Multifractal analysis of sputtered indium tin oxide thin film surfaces - Ţălu, Ştefan; Morozov, Ilya A.; Yadav, Ram Pratap (Applied surface science, 2019)
The aim of this study was to provide important insights into the micromorphology of sputtered indium tin oxide (ITO) prepared on glass substrates by direct current (DC) magnetron sputtering at room temperature using atomic force microscopy (AFM) and multifractal analysis. The samples were annealed at 450 °C in air and were divided into five groups to discuss the results, in correlation with the ambient combinations applied, as follows: I group, using argon (Ar); II group, using argon with oxygen (Ar + O2); III group, using argon with oxygen and nitrogen (Ar + O2 + N2); IV group, using argon with oxygen and hydrogen (Ar + O2 + H2); and V group, using argon with oxygen, nitrogen and hydrogen (Ar + O2 + N2 + H2). The VI group was the reference group. AFM was used to image the surface micromorphology in tapping mode, on square areas of 2 μm × 2 μm. The ITO thin film surfaces are characterized by 3-D (three-dimensional) nanometer-scale patterns highlighted by multifractal features which reflect the process used during the fabrication of thin films. In addition, the AFM images were stereometrically analyzed, in accordance with ISO 25178-2: 2012 and ASME B46.1-2009. The results have shown that the multifractal approach in correlation with the stereometric surface analyses are efficient tools for quantifying the 3-D surface microtexture changes at different fabrication combinations. [Display omitted] •We characterized the 3-D surface microtexture of sputtered indium tin oxide (ITO) thin films.•We determined the 3-D surface microtexture characteristics of samples at different fabrication ambient combinations.•We used atomic force microscopy (AFM), multifractal and stereometric analyses.•The 3-D micromorphology of surface samples exhibits multifractal features.